Applying Regional Citrate Anticoagulation in Continuous Renal Replacement Therapy for Acute Kidney Injury Patients with Acute Liver Dysfunction: a Retrospective Observational Study - Ying Yu; Sheng Peng; Zhongran Cen; Jing Cai; Wei Wang; Ying Tang; Meng Du; Zhanguo Liu; Ping Chang (Karger Publishers, 2018)
Background/Aims: Continuous renal replacement therapy (CRRT) is a treatment for acute kidney injury (AKI) patients. It has become a controversy about whether patients with liver dysfunction should perform CRRT with regional citrate anticoagulation (RCA). Methods: This retrospective observational study enrolled 145 AKI patients (275 CRRT sessions) who received CRRT with RCA and had no history of chronic liver disease. Circuit survival time, blood pressure, trans-membrane pressure (TMP), acid-base and electrolyte status were recorded and analyzed. The severity of liver dysfunction was determined by total bilirubin (TBil) and international normalized ratio (INR), while the accumulation degree of citrates was quantified by total/ ionized calcium (tCa/iCa) raito. Results: Our results showed that there was no correlation of tCa/iCa ratio with TBil or INR. And tCa/iCa ratio was not related to the disturbances of pH, lactates, sodium, magnesium, blood pressure or TMP despite that high tCa/iCa ratios might be related to the decrease of circuit survival time. TBil did not correlate with the above indexes, except for lactates levels. INR did not correlate with the above indexes except for lactates levels and blood pressure. In addition, neither was TBil, INR, nor tCa/iCa ratio, related with fatal outcomes (22.76% of the patients). Conclusion: The present study demonstrated that, with proper monitoring and adjustment of citrates and calcium infusion, applying RCA in CRRT is reasonably safe for AKI patients with acute liver dysfunction, as long as circuit time stays below roughly 50 hours.